2018
DOI: 10.1371/journal.pone.0205666
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide enhances the anti-metastatic effect of radiation in Ras-transformed cells via suppression of ERK–mediated MMP-2 activity

Abstract: BackgroundActivation of Ras oncogene in human tumors is associated with radiation-associated metastatic potential. Although ionizing radiation is one important method of cancer treatments, it has been shown to enhance matrix metalloproteinases (MMPs) activity and facilitates a more aggressive cancer phenotype. Our previous studies showed that andrographolide with lower dose rates of radiation could inhibit RAS-transformed cancer metastasis in vivo; however, the molecular mechanisms are not yet clear. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…We lysed cells with 100μl of PRO-PREP Protein Extraction Solution according to the manufacturer’s protocol. Then, protein samples (50 µg/well) were separated by 12% SDS-PAGE electrophoresis and transferred to PVDF membranes (at 260 mA for about 90 minutes), as reported previously ( 21 ). Briefly, membranes were blocked with 5% non-fat dried milk in 1X TBS-T buffer (for 1 hour at room temperature) and probed with primary antibodies (diluted with 5% non-fat milk in 1X TBST), followed by HRP-labeled secondary antibodies (also diluted with 5% non-fat milk in 1X TBST).…”
Section: Methodsmentioning
confidence: 99%
“…We lysed cells with 100μl of PRO-PREP Protein Extraction Solution according to the manufacturer’s protocol. Then, protein samples (50 µg/well) were separated by 12% SDS-PAGE electrophoresis and transferred to PVDF membranes (at 260 mA for about 90 minutes), as reported previously ( 21 ). Briefly, membranes were blocked with 5% non-fat dried milk in 1X TBS-T buffer (for 1 hour at room temperature) and probed with primary antibodies (diluted with 5% non-fat milk in 1X TBST), followed by HRP-labeled secondary antibodies (also diluted with 5% non-fat milk in 1X TBST).…”
Section: Methodsmentioning
confidence: 99%
“…Radiosensitivity is increased also by the inhibition of ERK-mediated MMP-2 activity (51) in the model of Ras-transformed cells (e.g., glioblastoma). The pro-apoptotic activity of vincristine and carbo-platinum in HNCC, through increase of ROS, are an example of chemosensitization finally affecting the AKT-p53 pathway (52)(53)(54). Sensitization of colon cancer cells to 5-fluorouracil (5-FU) is mediated by reduction of the p-MET level in the combination treatment (55).…”
Section: Cancermentioning
confidence: 99%
“…Previous studies showed that andrographolide has a potent inhibitor of wide verities of viruses, including influenza virus ( 37 , 38 ), hepatitis C virus ( 39 ), herpes simplex virus type 1 ( 40 ), Chikungunya virus ( 41 ). It also has the potential to inhibit the proliferation of lung carcinoma ( 42 ) and nasopharyngeal carcinoma ( 43 ), and tumor metastasis ( 44 ). Another report demonstrated that mice treated with andrographolide reduce the inflammation and fibrosis of damaged liver ( 45 ).…”
Section: Resultsmentioning
confidence: 99%